Prognostic significance of radiological bone involvement in childhood acute lymphoblastic leukaemia. Issue 7 (July 1977) - Masera, G; Carnelli, V; Ferrari, M; Recchia, M; Bellini, F
Abstract : In 98 children with acute lymphoblastic leukaemia, aged 1 to 12 years, the prognostic significance of radiological bone involvement was studied. The mean duration of remission and of survival was much shorter in cases with multiple bone involvement (3 or more bones) than in those where bone involvement was absent. In those cases presenting with 1 or 2 bone lesions no statement of prognostic significance can be made at this stage. A radiological skeletal survey should be made in all children presenting with leukaemia to identify those (about 15%) having multiple bone lesions and therefore a poor prognosis, in order that they can be given more intensive therapy.